Has public policy-making become a fully-fledged function of public administration in the Republic of Serbia? - Atanasijević Jasna; Vučetić Dejan (Zbornik Radova Pravnog Fakulteta u Nišu)
This paper examines the role of public policy-making by public administration in Serbia as one of the fundamental functions of public administration. By analyzing the normative framework and its application, the paper explores its historical development and advancement in recent decades. A set of regulations from 2018, including the Planning System Act and accompanying bylaws on the policy-making methodology, have laid the foundation for modern, evidence-based public policy in Serbia. Using qualitative methods, including normative-dogmatic and document analysis, the authors review the developments thus far and provide recommendations for further strengthening of this function of public administration in Serbia.